2018
DOI: 10.1017/dsj.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Affordance based interactive genetic algorithm (ABIGA)

Abstract: Designers can involve users in the design process. The challenge lies in reaching multiple users and finding the best way to use their input in the design process. Affordance based design (ABD) is a design method that focuses in part on the perceived or existing interactions between the user and the artifact. The shape and physical characteristics of the product enable the user to perceive some of its affordances. The goal of this research is to use ABD, along with an optimization tool, to evolve the shape of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The first experiment showed that an IGA can be used to interactively explore a sound design space and to define efficient solutions for a bi-objective optimisation problem. This is consistent with previous studies showing the application of IGAs as interactive design tools to address complex perceptual dimensions or affordances (Brintrup et al 2008; Mata et al 2018). In particular, when the two dimensions are conflicting, an IGA may provide efficient designs because interactions between variables are integrated during the interactive solutions search.…”
Section: Analysis/discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The first experiment showed that an IGA can be used to interactively explore a sound design space and to define efficient solutions for a bi-objective optimisation problem. This is consistent with previous studies showing the application of IGAs as interactive design tools to address complex perceptual dimensions or affordances (Brintrup et al 2008; Mata et al 2018). In particular, when the two dimensions are conflicting, an IGA may provide efficient designs because interactions between variables are integrated during the interactive solutions search.…”
Section: Analysis/discussionsupporting
confidence: 93%
“…More generally, the proposed method applies to any problem dealing with the optimisation of a parametrised design, according to one or several perceptual quantities, as long as the evaluation task is simple and short enough to allow for interactive optimisation. Thus, it is not limited to sound design, but can also apply to product shape design (e.g., Mata et al 2018). However, if the parameters take continuous values, the design recommendation method should be adapted (by, e.g., estimating probability density functions).…”
Section: Future Work and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We review here some use cases tackled with IGAs where the proposed method could readily be applied: design of automobile parts, like dashboards [19], steering wheels [20] and exterior shape of the vehicle [21]; clothing design [22][23][24][25]; design of furniture like glasses [2], bottles [26], vases [27] or chairs [28]. Each time, the aim is to find designs that best respond to a given semantic description (for example, a "sporty" dashboard).…”
Section: Applicability To Other Use Casesmentioning
confidence: 99%